A Comprehensive Step: A Book Review of Teachers Taking Action - Suzanne Porath (Networks: An Online Journal for Teacher Research, 2010)
Action research, as a term, has been around for over half a century, but it has only become accepted as legitimate research within the last two decades. In education, action research both challenges and is informed by traditional scholarly research and promises to empower teachers to become active participants, and not just consumers of university-based research. Cynthia Lassonde, an assistant professor at the State University of New York College, and Susan Israel, a literacy consultant, have provided an overview of the action research process in their book Teachers Taking Action: A Comprehensive Guide to Teacher Research, a 2008 monograph of the International Reading Association.